2016
DOI: 10.1016/j.seares.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Possible causes for growth variability and summer growth reduction in juvenile plaice Pleuronectes platessa L. in the western Dutch Wadden Sea

Abstract: 13Growth variability within individuals and among groups and locations and the 14 phenomenon of summer growth reduction has been described for juvenile flatfish in a 15 variety of European coastal areas whereby the underlying causes still remain elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Growth for most post-larval fish is dependent on a balance between access to sufficient prey resources and optimal thermal conditions (Ali et al, 2003;van der Meer, 2006;van der Veer, Jung, Freitas, Philippart, & Witte, 2016), as may be the case for halibut in the Eastern Bering Sea (area 4C/D). Physical conditions in the Gulf of Alaska (area 3A) are optimal during spring months, whereas in the summer surface temperatures can exceed the thermal optimum for extended periods (i.e., 2005, 2014, 2016; Figures 7a and 8a).…”
Section: Discussionmentioning
confidence: 99%
“…Growth for most post-larval fish is dependent on a balance between access to sufficient prey resources and optimal thermal conditions (Ali et al, 2003;van der Meer, 2006;van der Veer, Jung, Freitas, Philippart, & Witte, 2016), as may be the case for halibut in the Eastern Bering Sea (area 4C/D). Physical conditions in the Gulf of Alaska (area 3A) are optimal during spring months, whereas in the summer surface temperatures can exceed the thermal optimum for extended periods (i.e., 2005, 2014, 2016; Figures 7a and 8a).…”
Section: Discussionmentioning
confidence: 99%
“…p M ½ is the volume-specific maintenance cost, which is based on field data and hence also includes the cost for feeding and activity (e.g., swimming; van der Veer et al 2009). T A is Arrhenius temperature (in K), T ref is the reference temperature at which the assimilation rate is known, E m ½ is the maximum equilibrium reserve density that occurs at maximum food density (J/cm 3 ), and E G ½ is the energetic growth costs per unit of growth in structural body volume (J/cm 3 ; Van Der Meer 2006, van der Veer et al 2009). Fr is the metabolic and digestive enzyme fraction that is in its active state, which is temperature dependent (see Eq.…”
Section: Analysis Structurementioning
confidence: 99%
“…This hypothesis was supported by the observed late summer decrease in stomach content biomass in 0-group plaice, and especially of regenerating body parts of macrobenthic prey (Kuipers, 1977;de Vlas, 1979;. However, conclusions were hampered by the fact that field growth was estimated from shifts in mean size of the population over time, whereby bias such as size-selective predation and/or migration movements could not be excluded (van der Veer et al, 2016). To reduce this bias, the "summer growth reduction" hypothesis was re-evaluated for 0-group plaice using otolith microstructure analysis (Cardoso et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This lead to the formulation of the "maximum growth/optimal food conditions" hypothesis (sensu Karakiri et al, 1991, van der Veer & Witte, 1993: growth rates in these environments are maximum and mainly controlled by prevailing water temperatures. Since then, a variety of factors ranging from food quality and quantity (Karakiri et al, 1991;van der Veer & Witte, 1993), irreversible non-genetic adaptation (van der Veer et al, 2000a) and sex (van der Veer et al, 2016) have been identified as causes of growth variation in juvenile flatfish. In addition, there has been considerable debate on the existence of density -dependent food A C C E P T E D M A N U S C R I P T limitation (for overview see Le Pape & Bonhommeau, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation